Analisis Pengaruh Tingkat Kekayaan Daerah, Belanja Daerah, Ukuran Pemerintah Daerah, Leverage Dan Intergovernmental Revenue Terhadap Kinerja Keuangan Pemerintah Daerah(Studi Empiris Pada Pemerintah Daerah/Kota Se-Jawa Tengah 2011-2013) - Retnowati, Reny (2016)
The local government is required to produce a good financial performance so that people can assess government performance. This study aimed to analyze the influence of the local assets level , local purchase, the size of local governments, leverage and intergovernmental revenue on the financial performance of local governments. This study data using secondary data, financial reports of local governments / municipalities in Central Java in 2011-2013 have been published in www.djpk.kemenkeu.go.id. The sampling method was done by using purposive sampling. The sample in this study as many as 60 districts / cities during 2011-2013. This study uses multiple linear regression analysis model. The results showed that the local purchase and the size of local government are factors that affect the financial performance of local governments. While the level of local assets, leverage, and intergovernmental revenue has no effect on the financial performance of local governments.